Early diagnosis of co-existent ß-thalassemia and alkaptonuria - Lodh, Moushumi (Medknow Publications & Media Pvt Ltd, 2013)
Since the aggregate incidence of inborn errors of metabolism is relatively high, a high degree of suspicion is essential to correctly diagnose an inborn error of amino acid metabolism. We report a case of alkaptonuria an autosomal recessive disorder that occurs due to deficiency of homogentisic acid oxidasein a β-thalassemia infant presenting with reddish discoloration of nappies and clothes, breath holding spells, and microcytic hypochromic anemia. Born to consanguineous cousins, to our knowledge, the combination of β-thalassemia and alkaptonuria, which we have described in this baby, has not been reported earlier.